2003
DOI: 10.1016/s0009-8981(02)00333-9
|View full text |Cite
|
Sign up to set email alerts
|

Blood lead concentrations in children: new ranges

Abstract: Background-Lead exposure in young children may have adverse neurodevelopmental effects. Currently, an increased blood lead concentration is defined as ≥10 μg/dl for males and females of all ages, including children younger than 6 years. Using a large hospital population (n = 11,145), we define more specific ranges for pediatric blood lead concentrations.Methods-Pediatric blood lead concentrations were determined (atomic absorption spectrophotometry) on patient samples accrued from January 2001 to June 2002, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 15 publications
(12 reference statements)
1
13
0
1
Order By: Relevance
“…However, BLLs greater than 10 µg/dL continue to be more prevalent among children with known risk factors, including minority race or ethnicity; urban residence; residing in housing built before the 1950's; and low family income (CDC, 1991;CDC, 2002;Jones et al, 2009). For example, approximately 11,000 higher-risk children and adolescents who were tested from 2001 to 2002 at an urban medical center had higher BLLs than the NHANES sample; the geometric mean BLL was 3.2 µg/dL in males and 3.0 µg/dL in females (Soldin et al, 2003).…”
Section: Biomonitoring Informationmentioning
confidence: 95%
“…However, BLLs greater than 10 µg/dL continue to be more prevalent among children with known risk factors, including minority race or ethnicity; urban residence; residing in housing built before the 1950's; and low family income (CDC, 1991;CDC, 2002;Jones et al, 2009). For example, approximately 11,000 higher-risk children and adolescents who were tested from 2001 to 2002 at an urban medical center had higher BLLs than the NHANES sample; the geometric mean BLL was 3.2 µg/dL in males and 3.0 µg/dL in females (Soldin et al, 2003).…”
Section: Biomonitoring Informationmentioning
confidence: 95%
“…Annual mean Pb B were chosen from studies conducted in countries where lead had been banned from gasoline for at least 15-20 years (see references in Canfield et al, 2003;Dietrich et al, 1993;Ernhart et al, 1989;Lanphear et al, 2000;Martin et al, 2006;Oulhote et al, 2011;Schroijen et al, 2008;Smolders et al, 2010;Soldin et al, 2003;Tera et al, 1985;Thomas et al, 1999;Tong et al, 1998;Wasserman, 1997;Wietlisbach et al, 1995;Yaffe et al, 1983). Data were gathered regionally from North America, Australasia, northern and western Europe.…”
Section: Atmospheric and Blood Reviewsmentioning
confidence: 99%
“…One study [10] suggested that blood-lead levels (BLL) start increasing at six months when the children start to crawl and continues up to around age four when they are walking and there is consequently a decline. Other studies [11,12] have shown that BLL reached their highest concentration by 10 years of age and decreased thereafter.…”
Section: Introductionmentioning
confidence: 77%